The Influence of Environmental Awareness, Green Marketing, and Green Attributes Transparency on Purchase Intention Through Corporate Brand Image as a Mediating Variable: A Case Study on Unilever Consumers - Nurapni, Sinta; Ibrahim, Siti Sarah; Pratiwi, Delviana; Munawar, Muhammad Rasyid Khair (International Journal of Business, Law, and Education, 2024)
The purpose of this research is to analyze the direct influence of environmental awareness, green marketing, and green attributes transparency on brand image. It also aims to examine the impact of environmental awareness, green marketing, green attributes transparency, and brand image on purchase intention. Additionally, the study analyzes the influence of environmental awareness, green marketing, and green attributes transparency on purchase intention through brand image. The sample for this research consists of 100 respondents selected from Rinso customers in the Sukabumi region. Sample selection is done using non probability sampling, specifically Accidental sampling, and primary data is collected through questionnaires. The data analysis method involves Structural Equation Modeling (SEM), utilizing Partial Least Square (PLS) as the analytical tool and SmartPLS version 3.0 as the software for testing. The results indicate that the variable of environmental awareness does not have a direct and significant influence on brand image. However, both green marketing and green attributes transparency positively and significantly affect brand image. Green marketing and brand image directly influence consumer purchase intention positively and significantly. Nevertheless, environmental awareness and green attributes transparency, while showing a positive influence, do not reach statistical significance. Regarding indirect effects, brand image mediates the relationship between independent variables and purchase intention, except for the variable of environmental awareness.